A Novel Method to Examine Public Communications and Policy Representations: A Case Example of Hawai'i's Perspective on Juveniles Involved in Commercial Sexual Activity. (July 2022) - Marshall, Sarah Momilani
Public policy may be strongly influenced by the language used in the media to discuss issues. This language can create a policy image or policy representation that frames the issue as being either deserving or undeserving of policy aid. This policy representation, in turn, may influence the direction of public policies proposed to address the issue. This article presents the development of a codebook for systematically examining the language used in the media to create these policy representations. Framing theory and a qualitative content analysis approach were used to develop the codebook, using a 4-part taxonomy: problem definition, causal interpretation, moral evaluation, and policy recommendation. The issue of juveniles involved in commercial sexual activity in Hawai'i was used as a case study to guide creation of the codebook. Pilot study data were drawn from Hawai'i's local newspapers and from testimony submitted to the Hawai'i State Legislature during 1985-2016. A set of coding schemes built on the 4-part taxonomy was based on the dichotomous attitude of juvenile criminality and juvenile exploitation. Pilot data indicated that juveniles are increasingly being represented as victims of sexual exploitation (newspaper, 45%; testimony, 90%), and the presence of thematic elements in the media strongly correlated with this overall shift. A key lesson learned was the ability of the codebook to capture episodic and thematic elements, which may have strong implications for those concerned with populations that are exploited, politically marginalized, and in need of policy aid. Another key lesson learned was the strength of the codebook to collect quantitative and qualitative data that may lie outside carefully constructed dichotomous frames (eg, a policy representation of juveniles as survivors) and the media's prevailing narratives (eg, the experience of sexual minority juveniles).